Restoring degraded landscapes. A synthesis of evidence generated by the CGIAR Research Program on Water, Land and Ecosystems (WLE) to influence planning, investments, research, practice, capacity and policy - CGIAR Research Program on Water, Land and Ecosystems; International Water Management Institute (CGIAR Research Program on Water, Land and Ecosystems, 2021)
This synthesis brief draws on the experiences of the Restoring Degraded Landscapes sub-program, part of the CGIAR Research Program on Water, Land and Ecosystems (WLE). The brief captures learning from a decade (2011-2021) of research in development work with different stakeholders including farmers and governments across the world to reverse landscape degradation. It provides an overview of effective approaches, innovations and solutions that can be taken forward and scaled up to meet current and future challenges from land degradation – as well as the opportunities that may arise.